INTRODUCING PURPOSES IN WRITING. AUTHENTICITY IN WRITING PROCESS. GIVING FEEDBACK IN WRITING - SOBIROVA NOZIMA KOMILJONOVNA; MAMUROVA NAVRUZA SHERZODBEKOVNA; GAFOROV IKBOLJON UKTAMOVICH (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2023)
ABSTRACT: This article explores the importance of introducing purposes in writing, promoting authenticity in the writing process, and providing effective feedback. Writing with a clear purpose enhances motivation and engagement, while authentic writing experiences facilitate meaningful learning. Additionally, constructive feedback plays a crucial role in guiding students towards improved writing skills. The article emphasizes the significance of purposeful writing, authentic tasks, and targeted feedback in developing students' writing proficiency.